Negotiated Gender Equality in Multireligious Families: Muslim Minority Households in Tana Toraja - Abbas, Sitti Aisyah; Khatimah, Nur Husnul; Pajarianto, Hadi; Pribadi, Imam; Duriani, Duriani; Elihami, Elihami (Jurnal Ilmiah Al-Syir'ah, 2025)
This study examines the strategies employed by Muslim minority families in Tana Toraja to foster harmony and gender-balanced relationships within multireligious household settings. Using a qualitative phenomenological design, the research draws on extended interviews and close observations of five families formed through religious conversion. The analysis shows that everyday family life is shaped less by rigid patriarchal expectations than by negotiated understandings of roles and responsibilities, allowing men and women to construct a shared moral framework that remains sensitive to their differing religious commitments. Women, in particular, often act as stabilizing figures who sustain kinship networks through social participation, educational involvement, and economic activities, while simultaneously upholding clear boundaries in matters of worship and creed. Interpreted through Maqāsid al-Sharīʿah and contemporary approaches to Islamic pedagogy (Tarbiyah), these patterns reveal an egalitarian ethos that reinforces the protection of faith and lineage by fostering an atmosphere that is both tolerant of pluralism and grounded in religious integrity. The study contributes to current debates in Islamic family law and the sociology of religion by demonstrating how negotiated gender equality becomes a practical strategy for preserving familial cohesion in multireligious contexts.